Modeling and Simulation of Groundwater for Irrigational Usage in Ede City, Rivers State, Nigeria - Ukpaka, C.; Ezeilo, F. E.; Ozota, J. C. (International Journal For Research In Mechanical & Civil Engineering, 2018)
In this research the modified sodium absorption ratio differential equation developed for Ede City in Rivers State, Nigeria given as, - = 0 were solved using the approach of finite element method and the solution gives, SAR values for different weeks as = 0.36, = 0.35, and SAR values obtained by empirical model as = 0.36, = 0.35, . The concept of using finite element method in simulating and monitoring sodium absorption ratio was validated by comparing the relationship between results obtained by empirical model and finite element method using linear least square approach and coefficient of determination, = 0.844 indicating the reliability of finite element in simulating SAR values in groundwater of the study area. Describing the suitability of groundwater for irrigation usage, the groundwater is of low sodium water (S1) can be used for irrigation on almost all soil and for all crops except those which high sensitive to sodium, such as stone fruit trees and avocado and so on. In this research the modified sodium absorption ratio differential equation developed for Ede City in Rivers State, Nigeria given as, - = 0 were solved using the approach of finite element method and the solution gives, SAR values for different weeks as = 0.36, = 0.35, and SAR values obtained by empirical model as = 0.36, = 0.35, . The concept of using finite element method in simulating and monitoring sodium absorption ratio was validated by comparing the relationship between results obtained by empirical model and finite element method using linear least square approach and coefficient of determination, = 0.844 indicating the reliability of finite element in simulating SAR values in groundwater of the study area. Describing the suitability of groundwater for irrigation usage, the groundwater is of low sodium water (S1) can be used for irrigation on almost all soil and for all crops except those which high sensitive to sodium, such as stone fruit trees and avocado and so on.